2017
DOI: 10.1073/pnas.1710374114
|View full text |Cite
|
Sign up to set email alerts
|

FMRFamide-like peptides expand the behavioral repertoire of a densely connected nervous system

Abstract: Animals, including humans, can adapt to environmental stress through phenotypic plasticity. The free-living nematode can adapt to harsh environments by undergoing a whole-animal change, involving exiting reproductive development and entering the stress-resistant dauer larval stage. The dauer is a dispersal stage with dauer-specific behaviors for finding and stowing onto carrier animals, but how dauers acquire these behaviors, despite having a physically limited nervous system of 302 neurons, is poorly understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 107 publications
5
85
0
Order By: Relevance
“…Under normal cultivation conditions, activation of BAG neurons by hypoxia or CO 2 triggers an acute avoidance response and negative chemotaxis, indicating that environments with high CO 2 or low oxygen are aversive to C. elegans. BAGmediated avoidance behavior requires that BAG neurons release the neurotransmitter glutamate and neuropeptides (Lee et al, 2017;Guillermin et al, 2017;Hallem and Sternberg, 2008). These neurochemical signals act on interneurons of the RIA, RIG, AIY and AIZ types, some of which receive direct synaptic inputs from BAGs and all of which are required for CO 2 chemotaxis (Guillermin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal cultivation conditions, activation of BAG neurons by hypoxia or CO 2 triggers an acute avoidance response and negative chemotaxis, indicating that environments with high CO 2 or low oxygen are aversive to C. elegans. BAGmediated avoidance behavior requires that BAG neurons release the neurotransmitter glutamate and neuropeptides (Lee et al, 2017;Guillermin et al, 2017;Hallem and Sternberg, 2008). These neurochemical signals act on interneurons of the RIA, RIG, AIY and AIZ types, some of which receive direct synaptic inputs from BAGs and all of which are required for CO 2 chemotaxis (Guillermin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve organismal plasticity, it is has been shown that C. elegans dauer 580 entry involves the remodeling of glia and neural circuitry, as well as differential 581 expression of chemosensory and neuropeptide receptors [3,4,6,7,19]. While 582 dauer-induced remodeling of the AWC dendritic ends that increase their surface 583 area could heighten sensitivity, our results show that wild-type, daf-2, and daf-7 584 DL were actually less attracted than adults to several odors, and the DL of two daf-585 7 alleles even displayed avoidance of isoamyl alcohol.…”
Section: Elegans Dauers Have Attenuated Responses To Adult Odors 579mentioning
confidence: 99%
“…In C. elegans adults, the AWA neurons detect 2,3-butanedione 591 (diacetyl), while the AWC neurons sense isoamyl alcohol and 2,3-pentanedione. 592 A significant upregulation of neuropeptide expression during dauer entry occurs in 593 both C. elegans and P. pacificus [86], some of which may correlate with stage-594 specific olfactory behavior, as well as dauer-specific behaviors such as nictation 595 and the change in CO2 response valence [6]. A combination of cellular identity and 596 gene expression changes may be responsible for stage-specific chemosensory 597 behaviors between adults and DL [69,70].…”
Section: Elegans Dauers Have Attenuated Responses To Adult Odors 579mentioning
confidence: 99%
See 2 more Smart Citations